2016
DOI: 10.33096/jffi.v3i1.176
|View full text |Cite
|
Sign up to set email alerts
|

PENGEMBANGAN FORMULASI MIKROEMULSI MINYAK SEREH (Cymbopogon nardus) MENGGUNAKAN EMULGATOR SURFAKTAN NONIONIK

Abstract: Citronella oil (Cymbopogon nardus) is an essential oil which useful as an antibacterial that is usually provided in the form of macroemulsion for topical use. absorption of macroemulsion through the skin relatively low, thermodynamically is not stable and can produce a separate phase in the storage period. The one of development emulsion system to get better characteristics is to form a microemulsion. Microemulsion is an oil and water dispersion stable thermodynamically stabilized by surfactants and in some ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 0 publications
0
4
0
3
Order By: Relevance
“…According to Marques et al (2018), a fluid with this rheology has a velocity gradient that is perpendicular to the shear stress and a linearly proportional shear stress. These findings demonstrated that the preparation resembles a solution or liquid that flows readily since the droplets generated were smaller than emulsion (Hasrawati et al, 2016).…”
Section: Figure 1 the Nanoemulsion Of Avocado Oil Table 2 Avocado Oil...mentioning
confidence: 87%
“…According to Marques et al (2018), a fluid with this rheology has a velocity gradient that is perpendicular to the shear stress and a linearly proportional shear stress. These findings demonstrated that the preparation resembles a solution or liquid that flows readily since the droplets generated were smaller than emulsion (Hasrawati et al, 2016).…”
Section: Figure 1 the Nanoemulsion Of Avocado Oil Table 2 Avocado Oil...mentioning
confidence: 87%
“…Surfaktan nonionik mempunyai toksitas relatif rendah dan memiliki masing-masing nilai Hydrophilic Lipophilic Balance (HLB) tinggi, medium dan rendah (Suhendra et al, 2012). Hasrawati et al (2016) melaporkan bahwa penggunaan surfaktan nonionik pada pembuatan mikroemulsi relatif aman karena memiliki toksisitas dan sifat mengiritasinya rendah. Penggunaan tiga surfaktan dengan nilai HLB yang berbeda dapat membentuk mikroemulsi yang lebih stabil dibandingkan dengan dua campuran surfaktan atau hanya satu surfaktan (Sucitawati et al, 2021).…”
Section: Pendahuluanunclassified
“…Jika sistem pada sediaan memiliki ukuran partikel sangat kecil ketika dilewati cahaya, maka berkas cahaya akan diteruskan, sehingga warna larutan pada sediaan akan terlihat transparan dan hasil nilai persen transmitan akan semakin besar 21 . Dalam pengujiannya, aquadest digunakan sebagai blanko atau pembanding dikarenakan aquadest tidak memiliki partikel yang dapat menahan transmisi cahaya sehingga cahaya yang dilewatinya akan diteruskan tanpa adanya efek penghamburan cahaya, oleh karenanya aquadest memiliki nilai persen transmitan 100% 22 .…”
Section: Persentase Transmitanunclassified